2000
DOI: 10.1046/j.1365-2699.2000.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Chance and determinism in the development of isolated communities

Abstract: In the colonization of an island by potentially interacting species both the severity of the competition between them and the length of the interval between their arrivals should affect the likelihood of the second species becoming established. Between‐island variation in priority and the interval between colonizations will depend on the dispersal rates of the two species. We predict that early colonization should be relatively deterministic, whereas later in the colonization process both the sequence of arriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 29 publications
0
25
0
6
Order By: Relevance
“…However, available data do not allow any conclusions to be drawn about the comparative dispersion ability of the three species. In isolated ecosystems (as lakes and temporary ponds) also stochastic processes, for example the order of arrival of colonising species ("priority effects"), may play an important role in determining the structure of natural communities (Blaustein & Margalit 1996;Wilbur 1997;Ward & Thornton 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, available data do not allow any conclusions to be drawn about the comparative dispersion ability of the three species. In isolated ecosystems (as lakes and temporary ponds) also stochastic processes, for example the order of arrival of colonising species ("priority effects"), may play an important role in determining the structure of natural communities (Blaustein & Margalit 1996;Wilbur 1997;Ward & Thornton 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Under extreme conditions, priority effects ͑Eriksson and Eriksson 1998͒ may produce novel species assemblages ͑cf. Roozen and Westhoff 1985;Facelli and D'Anela 1990;del Moral and Wood 1993;Ward and Thornton 2000͒. Within-plot similarity does indeed decline with distance from sources and with elevation. This effect recalls long-term studies of small islands in a Swedish lake ͑Rydin and Borgegård 1991͒, where similarity increased over time, but where further development appeared arrested because dominant trees have failed to reach the islands.…”
Section: Similaritymentioning
confidence: 97%
“…Beside the long debate on equilibrium and non equilibrium hypotheses (see Naselli-Flores et al, 2003), some studies on assembly rules revealed that the structure of a community may depend on a priority effect (Ward & Thornton, 2000) modulated by complex hierarchical factors (Rodrigo et al, 2009). Hierarchy theory is a formal approach to the complex influences of scale, and suggests that different phenomena (e.g.…”
Section: Introductionmentioning
confidence: 99%